Detecting formal thought disorder by deep contextualized word representations - Sarzynska-Wawer, Justyna; Wawer, Aleksander; Pawlak, Aleksandra; Szymanowska, Julia; Stefaniak, Izabela; Jarkiewicz, Michal; Okruszek, Lukasz (Psychiatry research, 2021)
•NLP algorithm can detect features of formal thought disorder (FTD).•Deep contextual word representations may be used to improve detection of the FTD.•NLP accuracy is comparable to observer’s ratings. Computational linguistics has enabled the introduction of objective tools that measure some of the symptoms of schizophrenia, including the coherence of speech associated with formal thought disorder (FTD). Our goal was to investigate whether neural network based utterance embeddings are more accurate in detecting FTD than models based on individual indicators. The present research used a comprehensive Embeddings from Language Models (ELMo) approach to represent interviews with patients suffering from schizophrenia (N=35) and with healthy people (N=35). We compared its results to the approach described by Bedi et al. (2015), referred to here as the coherence model. Evaluations were also performed by a clinician using the Scale for the Assessment of Thought, Language and Communication (TLC). Using all six TLC questions the ELMo obtained an accuracy of 80% in distinguishing patients from healthy people. Previously used coherence models were less accurate at 70%. The classifying clinician was accurate 74% of the time. Our analysis shows that both ELMo and TLC are sensitive to the symptoms of disorganization in patients. In this study methods using text representations from language models were more accurate than those based solely on the assessment of FTD, and can be used as measures of disordered language that complement human clinical ratings.